Why gold?: the one sure cure for inflation and economic tyranny - Snyder, Leslie (New York: Exposition Press, 1974)
The book is to dispel the ignorance surrounding the nature of coin, credit and circulation. It also shows how to stop inflation and its destructive results, and how to return to monetary freedom and sanity-the Gold Standard.
Bibliography: p. 149.
usc 28/8/17
Loans
Keywords: Gold standard; Inflation (Finance); Currency question; United States